Structural basis for the conformational changes of insulin receptor induced by three different hormone ligands - Zhang, Xi; Zhang, Ting; Wu, Cang; Gao, Yuanzhu; Zhang, Shuo; Li, Zhenglin; Zhong, Linshan; Xia, Chenyu; Yang, Liuqing; Dong, Fengquan; Shu, Qing; Fu, Yang; et al. (浪淘沙预印本平台, 2026)
The insulin receptor (IR) is central to the regulation of glucose and lipid metabolism. Although insulin is its primary ligand, insulin-like growth factors I and II (IGF-I and IGF-II) also engage IR, albeit with reduced affinity. The structural basis of cooperative ligand binding, however, has remained poorly understood. Here, we report cryo-Electron Microscopy (cryo-EM) structures of IR in complex with insulin, IGF-I, and IGF-II, revealing that all three ligands engage the receptor at overlapping binding sites and can induce a conserved T-shaped quaternary assembly involving four ligand molecules at site 1/1′ and site 2/2′. Despite this shared overall architecture, distinct ligand-specific conformational changes were observed. Notably, IGF-I and IGF-II adopt different binding sequence at site 1 and site 2 compared to insulin, suggesting unique interaction dynamics. These structural insights highlight divergent mechanisms of ligand recognition and cooperative binding, providing a deeper understanding of hormone-induced conformational modulation of the IR.